Development of single input polarization-sensitive optical coherence tomography, towards local birefringence imaging with high resolution and lower cost - Xiong, Qiaozhou (Nanyang Technological University, 2020)
Optical coherence tomography (OCT), as a non-invasive imaging method, has been established as a standard diagnostic technology in clinics during the last 25 years. The current OCT can provide depth-resolved imaging, but lacks property resolved information and does not have enough spatial resolution to resolve micrometer scale structures. To address the former issue, polarization-sensitive OCT (PS-OCT) has been developed as a powerful technology to evaluate the distribution of collagen fibers, smooth muscle cells, nerve fibers, etc., which exhibit birefringence, an optical property leading to delay between light polarized in orthogonal directions. PS-OCT can be categorized into single input PS-OCT and multiple inputs PS-OCT according to the number of input polarization states. Single input PS-OCT has been widely applied in many fields such as ophthalmology, cardiology, and dermatology, due to its simplicity. To address the latter issue, ultrahigh resolution OCT and Micro-OCT have been developed to resolve cellular and subcellular structures relevant to disease diagnosis. My research aims to develop theoretical frameworks and novel instrumental methods for the realization of single input PS-OCT with high resolution. Intuitively, it’s straightforward to achieve ultra-high resolution in PS-OCT. However, broad bandwidth which is essential for ultra-high resolution magnifies the effects of imperfect polarizing elements and the fall-off imbalance of dual spectrometers for polarization diverse detection. In this thesis, based on Jones matrix formalism, the polarization distortions were modeled and calibrated. The proposed method yields lower polarization distortion and provides more reliable contrasts especially when the sample birefringence is weak. The polarization distortion correction was demonstrated with tissue phantoms as well as animal tissues. On the other hand, single input PS-OCT usually cannot provide local birefringence imaging, which is more intuitive than its accumulative counterpart. Enabling local birefringence imaging using single input would alleviate the hardware requirements of PS-OCT and would enable more widespread exploration of this compelling contrast mechanism. This simplification is possible with the mirror state constraint discovered in this work: the polarization state of backscattered or reflected light, when measured through identical illumination and detection paths, frequently evolved through the employed input polarization state but with reversed handedness, corresponding to the input state mirrored by the horizontal plane of the Poincaré sphere. We validated this constraint both theoretically and experimentally using technical phantoms of known birefringence. I further successfully demonstrated the local retardation imaging with single input PS-OCT both in free-space and fiber-based implementations with the mirror state constraint. Phantom imaging and animal ocular tissue imaging ex vivo were performed to validate the performance and clinic potential. An important application of the mirror state constraint is to realize single input polarization-sensitive intravascular optical frequency domain imaging (OFDI), where the illumination polarization state changes when propagating through a rotating catheter which mandates two polarization inputs. Achieving reliable measurements of local retardation with single input polarization state will be of great commercial interest. We demonstrate the reliability of the single input processing with Bland Altman analysis when comparing the results with multiple input PS OFDI. In conclusion, this thesis research advances the field in the following aspects. It provides working methods to correct the polarization distortions in the high-resolution PS-OCT for the first time; this thesis research also elucidated the polarization evolvement trace along with the depth in the back-scattering system and established the mirror state constraint, a novel theoretical framework. This thesis further uses this constraint to enable local birefringence imaging using single polarization input in both free- space and fiber-based systems and demonstrates single input polarization sensitive intravascular OFDI with performances comparable to the dual inputs benchmark.